Deteksi Risiko Diabetes Mellitus Tipe 2 Menggunakan FINDRISC - Firda ch Panna; Iren Heni Mahakena; Neneng Pratiwi; Ayu Rambu; Venti Agustina (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Diabetes mellitus is often not detected before a diagnosis is made, so that morbidity (occurrence of diseases or conditions that change health and quality of life) and early mortality (death) is very high. So that it is important early detection as early as possible provides an opportunity to be able to control the rate of morbidity and mortality of DMs. The purpose of this community service is to predict the risk of developing type 2 diabetes mellitus by using the FINRISC (The Finnish Diabetes Risk Score) tool which has been validated with 8 components. The results of the service obtained those 15 respondents were detected using this measuring instrument with the results that 6 people were in the slightly increased risk category (score 7-11), 5 people were in the moderate risk category (score 12-14) and 4 people were in the high risk category (score). 14-20). It can be concluded that the higher the total score obtained, the individual has a very large chance of having diabetes in the future.